Remembering preservation in hippocampal amnesia. [article]. - Clark, Ian A.
The lesion-deficit model dominates neuropsychology. This is unsurprising given powerful demonstrations that focal brain lesions can affect specific aspects of cognition. Nowhere is this more evident than in patients with bilateral hippocampal damage. In the past 60 years, the amnesia and other impairments exhibited by these patients have helped to delineate the functions of the hippocampus and shape the field of memory. We not question the value of this approach. However, less prominent are the cognitive processes that remain intact following hippocampal lesions. Here, we collate the piecemeal reports of preservation of function following focal bilateral hippocampal damage, highlighting a wealth of information often veiled by the field's focus on deficits. We consider how a systematic understanding of what is preserved as well as what is lost could add an important layer of precision to models of memory and the hippocampus. (from the authors)